CARACTERIZAÇÃO TÉRMICA, REOLÓGICA E ESTRUTURAL DE AMIDOS DE MANDIOCA NATIVO, ÁCIDO-MODIFICADO E OXIDADO EXPOSTOS A RADIAÇÃO DE MICRO-ONDAS - Colman, Tiago Andre Denck (2013)
Samples of acid-modified and oxidised untreated cassava starch were exposed to microwave radiation for periods of five, ten and fifteen minutes. Immediately after these exposure periods the temperature of each starch sample was measured, which was at a maximum of 135 °C. All samples were analysed by thermogravimetry and derivative thermogravimetry (TG/DTG); differential scanning calorimetry (DSC); rapid viscoamylographic analysis (RVA); X-ray diffraction powder, and non-contact atomic force microscopy (NC-AFM). Colour characteristics were determined by reflectance spectrophotometry. Thermal behaviour, gelatinisation temperature, enthalpy, and paste and structural properties were determined. Viscosity gradually decreased with increasing exposure to microwaves for the samples of untreated and oxidised starch samples. The acid-modified starch failed to show pasting properties during all the periods of exposure to radiation. The relative degree of crystallinity (%) increased with the acid-modification and decreased with increasing exposure time to microwave radiation. The micro images obtained by NC-AFM showed a gradual increase in the diameter of the granules of the acid-modified and oxidised starches; for the samples of untreated starch no significant variation was observed in the granule diameter after exposure to microwaves. Reflectance spectrophotometry showed that there was a progressive change in colour due to the microwave action causing a trend mainly to yellow for all the studied samples.